Spatial adaptation patterns and coordinated development of water-energy-food complex system in the yellow river basin - Yingdong Hou; Guoying Zhao; Yujing Liu; Xiaoyang Li (Scientific Reports)
Abstract The coordination development of the Water-Energy-Food complex system (WEF CS) is vital to realizing the Sustainable Development Goals of the United Nations. However, the existing research ignores the influence of external environment, and it is not clear which dimension is the key driving mechanism for coordinated development of WEF CS. Herein, it built a theoretical framework of “system unit-nexus-natural environment” WEF CS based on the logical framework of “unit-nexus-external environment”, and adopted Dagum Gini coefficient, coupling coordination degree, and grey correlation models to explore the sustainable development ability of water resource, energy resource and food resource of the Yellow River Basin (YRB). It showed that (1) the overall development level of WEF CS showed significant stage differences, indicating upstream > downstream > midstream; (2) the overall Gini coefficient decreased from 0.123 in 2004 to 0.084 in 2020, and the spatial mismatch of development level mainly came from the difference between reaches; (3) the influencing factors of the key zones that hindered the development of WEF CS chiefly came from the nexus dimension. This study provides insights into optimizing spatial adaptation pattern and improving coordination development in basins.